Attila nutritus in Engadi or the knowledge of late antique historical geography in mediaeval Hungarian chronicles - Grzesik, Ryszard; Kotłowska, Anna (Balcanica Posnaniensia. Acta et studia, 2024)
The 10th chapter of the Chronica de Gestis Hungarorum written by Simon of Kéza contains a puzzling phrase: Attila (...) nutritus in Engadi. So far, no attempt has been made to explain it. According to the authors of the following article, Simon took it from the Latin translation of the Onomasticon of Eusebius of Caesarea (d. 339) by St. Jerome. In all likelihood, Simon gained access to Jerome’s codex during his trip to southern Italy. It is necessary to distinguish three stages of the rise and change of the scholarly tradition about Attila as the ancestor of the Arpad dynasty and the Huns as the ancestors of the Hungarians: 1) Attila is viewed as the ancestor of Almos and Arpad; 2) Aquila in the Hungarian-Polish Chronicle as the founder of the Hungarian state, which was an attempt at a Christian rationalization of the story of the Turul, an ethnogenetic story about the Hungarians and their dynasty; 3) the inclusion of the Huns in Hungarian history by Simon of Kéza while removing Attila from among the ancestors of the dynasty. The mention of Engaddi (attesting to Simon's knowledge of the latin topography of Palestine, ultimately derived from Eusebius of Caesarea) likens him to the biblical David showing that, like the great warrior-king of Judah and Israel, Attila was the preeminent ruler of the Huns, i.e. the Hungarians, and at the same time legitimizes him, placing him, and, not least, his people, in the horizon of the world of Mediterranean civilization.